Genetic algorithm based examination timetabling system - Hernandez,Krishna Bacalso (2006)
The genetic algorithm-based examination timetabling system was developed for creating feasible and acceptable final examination timetables for the undergraduate degree programs of the University of the Philippines in Mindanao. It responds to the need of the university on handling an increasing occurrence of conflict in producing final examination timetables due to the increasing number of students in the university and the implementation of the revised general education program (RGEP). The developed system generates batched timetables for further analysis and selection where the details of constraint violation are described. The use of genetic algorithm is described in detail to further illustrate the functionality of the system. Genetic algorithm is used both in generating initial feasible timetables and in optimization to create acceptable timetables
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2006
Keywords: Genetic algorithm; Timetabling system